2004
DOI: 10.1063/1.1782260
|View full text |Cite
|
Sign up to set email alerts
|

X-ray fluoresced high-Z (up to Z=82) K x rays produced by LiNbO3 and LiTaO3 pyroelectric crystal electron accelerators

Abstract: High-energy bremsstrahlung and K X-rays were used to produce nearly background-free K X-ray spectra of up to 87 keV (Pb) via X-ray fluorescence. The fluorescing radiation was produced by electron accelerators, consisting of heated and cooled cylindrical LiTaO 3 and LiNbO 3 crystals at mTorr pressures. The newly discovered process of gas amplification whereby the ambient gas pressure is optimized to maximize the electron energy was used to produce energetic electrons which when incident on a W/Bi target gave ri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Our analysis techniques provide a methodology for assessing the potentials of particular PY material and its 2-2 laminates for applications under OC condition. For instance, appraising employment credentials of LTO or LNO in applications such as PY X-ray generation, [4][5][6] electron accelerator, 7 and nuclear fusion. 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis techniques provide a methodology for assessing the potentials of particular PY material and its 2-2 laminates for applications under OC condition. For instance, appraising employment credentials of LTO or LNO in applications such as PY X-ray generation, [4][5][6] electron accelerator, 7 and nuclear fusion. 8…”
Section: Discussionmentioning
confidence: 99%
“…͑2͒, describes the pyroelectricity of any PY material experiencing strain under SC condition. However, in practice, some applications such as PY X-ray generation, [4][5][6] electron accelerator, 7 and nuclear fusion 8 are conducted under conditions most closely approximated by open circuit ͑OC͒. We believe there is a difference between the PY coefficient under OC and SC conditions, and it is paramount that this disparity between the two be formulized to provide better insights into these applications of pyroelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…The PY materials investigated are PZT, such as PZT-5H and PZT-5A, barium titanate ͑BTO͒, PVDF, and lithium tantalate ͑LTO͒ and lithium niobate ͑LNO͒ for their deployment in applications such as PY x-ray generation 27,28 and electron accelerators. 29 The analysis on LTO and LNO will mainly be dealt in our other publication 30 since their application utilizes PY coef. under open circuit condition.…”
Section: Various Py and Np Materials Consideredmentioning
confidence: 99%
“…Brownridge's first publication 5 showed that emission from a CsNO 3 crystal could cause characteristic L-shell x-ray emission from gold (9.71 and 11.44 keV) if the crystal was slowly heated from 77°K to 150°K. He later improved his technique by using LiNbO 3 and LiTaO 3 crystals, with which he was able to fluoresce the k-shell of lead 44 (74.96 and 84.92 keV).…”
Section: X-ray Generation With Pyroelectric Crystalsmentioning
confidence: 99%